Liver Abscess Secondary to Duodenal Perforation After Fishbone Ingestion: A Case Report - Rodriguez, Fernanda Pombo; Zangari, Matheus Antônio Chiconelli; Piltcher-da-Silva, Rodrigo; Sasaki, Vivian Lais; Felisberto, Doroty Eva Garcia; Coelho, Júlio Cezar Uili; Ramos, Eduardo José Brommelstroet; Fortunato, Micheli (Brazilian Journal of Case Reports, 2024)
Even though ingestion of a foreign body is a common situation in the emergency department, the complications of a perforation of the gastrointestinal tract that develops into a liver abscess are rare. Early suspicion and diagnosis lead to lower morbidity and mortality. This case involves a 63-year-old man who had a history of swallowing a fish bone, followed by abdominal pain, fever and vomiting. The diagnosis of liver abscess due to possible perforation of the duodenum was made on abdominal tomographic imaging. Far from removal, the usual treatment for foreign bodies in the gastrointestinal tract, the decision was made in this case to leave the stent in situ, combined with transhepatic percutaneous drainage of the abscess and endovenous antibiotics. The patient developed well with early discharge from hospital and outpatient follow-up care.